Pengaruh Kombinasi Dosis Pupuk NPK dan Konsentrasi Pupuk Organik Cair Limbah Buah-Buahan Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) Varietas Gustavi F1 - Solihat, Ririn Mar'atun; Syah, Bastaman; Laksono, Romi Andhika (UNIVERSITAS LABUHANBATU, 2025)
Tomato production in West Java has decreased in 2021-2023 due to suboptimal cultivation practices, especially in the continuous use of chemical fertilizers with excessive doses. The use of liquid organic fertilizers is one potential solution. The research method used is an experimental method, using a single factor Randomized Block Design (RAK) consisting of 9 treatments and repeated 3 times, with treatments consisting of A (NPK 300 kg + POC 0 ml), B (NPK 240 kg + POC 2 ml), C (NPK 240 kg + POC 4 ml), D (NPK 240 kg + POC 6 ml), E (NPK 240 kg + POC 8 ml), F (NPK 180 kg + POC 2 ml), G (NPK 180 kg + POC 4 ml), H (NPK 180 kg + POC 6 ml), I (NPK 180 kg + POC 8 ml). The observation data were analyzed by analysis of variance and further tested with the Duncan Multiple Range Test (DMRT) at a level of 5%. The results of the F test showed that there was a significant effect of the combination of NPK fertilizer doses and the concentration of liquid organic fertilizer from fruit waste on the growth and yield of tomato plants (Solanum lycopersium) of the Gustavi F1 variety. The DMRT test showed that treatment E (NPK 240 kg + POC 8 ml) gave the highest results on the average parameters of plant height 78.187 cm, Number of leaves 22.6 stalks, Stem diameter 9.387 mm, Fruit weight per grain 51.635 g, Number of fruits per plant 15.333 grains, Fruit weight per plant 792.667 g, Fruit sweetness level (Brix) 7.667. Keywords: NPK fertilizer, liquid organic fertilizer, tomato